CSR DISCLOSURE AND COST OF CAPITAL : THE MEDIATING ROLE OF EARNINGS QUALITY - Chaerunnisa .; Tri Lestari; Windu Mulyasari (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2021)
This study aims to analyze the effect of CSR disclosure on the cost of capital with earnings quality as mediating variable. CSR disclosure was measured by Global Reporting Initiative (GRI) Standards. The cost of capital was measured by the cost of equity and the cost of debt. Meanwhile, earnings quality was measured by absolute abnormal accruals. The population of this research is mining companies listed on the Indonesia Stock Exchange period 2017-2019. Based on the purposive sampling method, the samples chosen are 32 companies with a total sample of 96 data. This study used multiple linear regression analysis using SPSS 25 version software and path analysis using the Sobel online calculator. This study showed that CSR disclosure has a direct negative effect on the cost of equity but does not affect the cost of debt. Firms with better CSR disclosure have better earnings quality. Earnings quality does not affect both costs of capital proxies. Earnings quality does not have a mediating role in the effect of CSR disclosure on both costs of capital proxies.